IMPLEMENTASI ANALYTIC HIERARCHY PROCESS (AHP) DALAM SISTEM PENDUKUNG KEPUTUSAN UNTUK OPTIMALISASI SELEKSI ATLET BOLA BASKET BERBASIS MULTIKRITERIA - Erie Abdan Amirullah Faqih; Okta Irawati (LPPM Politeknik Pratama Kendal, 2026)
The selection process for the best athletes at the Indonesian Basketball Association (PERBASI) Serang Regency remains characterized by a reliance on the subjective discretion of coaches, which implies a deficit in transparency and objectivity. This condition potentially triggers decision inconsistencies and organizational internal friction. This research aims to construct and implement a Decision Support System (DSS) to mitigate these issues. The primary methodology adopted is the Analytic Hierarchy Process (AHP), which is capable of analyzing multi-criteria problems through measurable priority weighting. The evaluation criteria employed encompass Dribbling, Passing, Shooting, Defense, and Speed & Agility. System development was executed using the Waterfall life cycle, with primary data obtained through interview and observation techniques. Implementation results confirm that the AHPbased DSS has been validated as capable of facilitating a more efficient and objectively measurable decision-making process. The AHP calculations yield the best athlete recommendation, namely Alfri (A2), with the highest Global Priority weight of 0.512. Consequently, the application of this AHP framework significantly contributes to reducing subjective bias and optimizing the speed of the athlete selection cycle